A Feature Model for an IDE4OCL - Chimiak-Opoka, Joanna; Demuth, Birgit (Electronic Communications of the EASST, 2011)
An Integrated OCL Development Environment (IDE4OCL) can significantly improve the pragmatics and practice of OCL. Therefore we started a comprehensive requirement analysis with the long term vision of a multisite IDE4OCL project. In this paper we present a feature model for the IDE4OCL vision based on this analysis. In an earlier work we identified domain concepts, tool–level interactions with IDE4OCL, and use cases for OCL developers including a set predefined features. In the second step, we asked the OCL community members for their feedback on our proposal. Around 100 researchers, tool developers and practitioners who gained experience with OCL have voted in an online–survey. The results gave us a valuable insight in the needs of OCL usage both in usual and advanced OCL applications. One of the important results is a collection of features that have been proposed additionally to our predefined features. We analysed all the comments of the participants of the survey and consolidated them into an extended set of IDE4OCL features and eventually into a feature model.